Sustainability analysis and decision-making strategy for swamp buffalo (Bubalus bubalis carabauesis) conservation in Jambi Province, Indonesia - Syarifuddin, Hutwan; Afdal, Muhammad; Yurleni Yurleni; Hamidah, Afreni; Devitriano, Dodi; Poy, Tee Tuan (Walter de Gruyter, 2024)
The objective of this study is to analyze the sustainability of swamp buffalo cultivation and develop decision-making strategies. Data were collected through focus group discussions with key informants in swamp buffalo cultivation and surveys of buffalo farmers in three regencies in Jambi Province. This study examines 37 attributes contained in four dimensions: ecological, economic, social, and technological dimensions. Data were analyzed using multidimensional scaling through the Rapid appraisal for buffalo technique and analytical hierarchy process (AHP) The results showed that the sustainability index of swamp buffalo cultivation in Sarolangun Regency was 59.39%, Batanghari 58.23%, and Tebo 55.93%. This study identified 12 leverage attributes obtained from 37 attributes that affect the sustainability of swamp buffalo, i.e., forage feed, agricultural waste, land use, agricultural infrastructure, land ownership, buffalo manure, buffalo ownership, livestock motivation, environmental impact, agricultural waste treatment, land processing, and post-harvest technology. Then, from the results of four-dimensional weighting with 12 attributes using AHP, there are 5 alternative strategies in decision making, namely, (1) build internet network infrastructure, (2) determine the number of livestock that can be raised in an area, (3) establish buffalo farming institutions, (4) prevent land use conflicts, and (5) increase farmer participation in raising buffalo livestock. This research provides input to policy makers to develop swamp buffalo cultivation by considering ecological, economic, social, and technological dimensions.